2012
DOI: 10.1007/jhep08(2012)148
|View full text |Cite
|
Sign up to set email alerts
|

Null Energy Condition violations in bimetric gravity

Abstract: We consider the effective stress-energy tensors for the foreground and background sectors in ghost-free bimetric gravity. By considering the symmetries of the theory, we show that the foreground and background null energy conditions (NECs) are strongly anti-correlated. In particular, the NECs can only be simultaneously fulfilled when they saturate, corresponding to foreground and background cosmological constants. In all other situations, either the foreground or the background is subject to a NEC-violating co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 50 publications
1
53
0
Order By: Relevance
“…Another interesting general feature of the bimetric solutions was noticed in [180]. There it was found that the effective stress-energy tensors that the bimetric interactions generate, i.e.the negative of V g mn and V f mn , never satisfy the null-energy condition simultaneously unless the two metrics are proportional.…”
Section: General Propertiesmentioning
confidence: 91%
See 1 more Smart Citation
“…Another interesting general feature of the bimetric solutions was noticed in [180]. There it was found that the effective stress-energy tensors that the bimetric interactions generate, i.e.the negative of V g mn and V f mn , never satisfy the null-energy condition simultaneously unless the two metrics are proportional.…”
Section: General Propertiesmentioning
confidence: 91%
“…There it was found that the effective stress-energy tensors that the bimetric interactions generate, i.e.the negative of V g mn and V f mn , never satisfy the null-energy condition simultaneously unless the two metrics are proportional. In more detail [180], found that if k m is a null-vector with respect to g , . Furthermore the inequalities only saturate for proportional solutions, when the interactions reduce to pure cosmological constant contributions (see section 5.3.1).…”
Section: General Propertiesmentioning
confidence: 99%
“…Therefore, although the existence of wormholes and bouncing cosmologies required violations of the NEC in general relativity, in modified gravity theories the NCC could be violated by material content satisfying the NEC. In that case, it is possible to define an effective stress-energy tensor putting together the modifications with respect to general relativity that violates the NEC [62,[70][71][72][73][74]. As this effective tensor is not associated with matter, there is no reason to require that it had some a priori characteristics.…”
Section: Limitations Of the Standard Energy Conditionsmentioning
confidence: 99%
“…Therefore, one can impose that the WEC be satisfied for the matter stressenergy tensor, but there is no reason why the energy density associated with the effective stress-energy tensor should be positive, since this tensor just encapsulates the modification with respect to GR [21,25]. Indeed, in some theories one can easily obtain T (eff) ab k a k b < 0; see, for example, [48,49]. Following this spirit, in alternative theories of gravity one can obtain geometries where the NCC is violated supported by a material content with a positive energy density as measured by any observer.…”
Section: Effective Phantom Behaviormentioning
confidence: 99%